Assessment of Nutrient and Sediment Loads in Buhisan, Bulacao and Lahug Rivers, Cebu, Philippines - Maglangit, Fleurdeliz F; Galapate, Ritchelita P; Bensig, Eukene O (International Journal of Sustainable Energy and Environmental Research, 2016)
The study aimed to provide baseline data by assessing the nutrient levels and sediment load in Buhisan, Bulacao and Lahug Rivers. Specifically, the study assessed the nitrates, Total Phosphorus (TP), Total Suspended Solids (TSS) and Total Dissolved Solids (TDS) concentrations of the rivers. Water samples were taken by grab sampling from three designated sites (upstream, midstream and downstream) along each river. Laboratory analyses were performed according to standard protocols. Results of the study were compared with the standard set by the Department of Environmental and Natural Resources (DENR). The nitrate, TSS and TDS levels did not exceed the allowable concentration set by the government but the TP did. The mean TP values observed at Buhisan, Bulacao and Lahug Rivers ranged from 0.10-1.82 mg∙L-, 0.05-0.48 mg∙L-, and 0.17-2.75 mg∙L-, respectively. The TP levels in the midstream and downstream areas of Buhisan and Lahug Rivers exceeded the 0.4 mg∙L- limit. High TP levels could be attributed to anthropogenic sources like untreated domestic waste discharges, unsanitary sewer systems in the surrounding communities, and runoffs from fertilized backyard gardening, and piggery.